The First Diplomatic Mission of Romania in Portugal (1880) - Iliescu, Mircea (Acta Universitatis Danubius. Relationes Internationales, 2023)
In March 1880, the first Romanian diplomatic mission was sent to Spain and Portugal, led by Alexandru Plagino, seconded by Dimitrie Bărcănescu. The Spanish and Portuguese Crowns would be willing to recognize the independence of Romania in the context of the end of the Russian-Turkish War of 1877-1878, the Treaty of Berlin, 1878, and the previous recognition by the Great Powers. The objective of the mission was to strengthen bilateral diplomatic relations.